Effects of Extravasation Prevention Practice Guideline on Extravasation in Patients with Cancer Undergoing Chemotherapy - Maneerat, Sureeporn; Namvongprom, Ampaporn; Pakdevong, Nam-oy (NU Journal of Nursing and Health Sciences, 2019)
This Post-Test Only Control Group Design study aimed to investigate the effects of Extravasation prevention practice guideline on Extravasation in patients with cancer receiving FOLFOX regimen chemotherapy. A purposive sampling of 70 patients admitted to ward 14 of Chulabhorn Hospital during August 2017 to July 2018 was recruited for this study. 44 patients in comparison group received a standard care, 26 patients in intervention group received evidence-based care. Extravasation was assessed and collected during a cycle of chemotherapy. Data were analyzed using descriptive statistics and Fisher's Exact test. The findings showed that 6 patients (13.64%) in the comparison group had grade 2 Extravasation injuries while there was none in the intervention group. Fisher's Exact test found that there was no difference between the two groups (p = .078). Replication of research and increasing the number of subjects is also suggested.